73.5k views
2 votes
PLEASE ANSWER THIS AND EXPLAIN HOW YOU GOT THE ANSWER.

9 - 3 ÷ 1/3 + 1 =

2 Answers

1 vote


9 - 3 / (1)/(3) + 1 =

Divisions go first, to do it we have to reverse the fraction and turn ÷ into ×


= 9 - 3 * 3 + 1 =

Now the multiplication


= 9 - 9 + 1 =


= 1

User Richard Hauer
by
5.7k points
6 votes

Answer:

Explanation:

If you use pemdas, you would do 3÷1/3 which equals 9. Then do 9-9, which equals 0. Then, do 0+1, which equals 1. Hope this helps! <3

User Dallas Johnson
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.